Labor, Employment, and Social Policies in the EU Enlargement Process : Changing Perspectives and Policy Options - Funck, Bernard; Pizzati, Lodovico (Washington, DC: World Bank, 2013)
Transition has been a wrenching process for the labor markets of Central and Eastern European countries (CEECs), and the prospect of joining the European Union gives rise to both hopes and misgivings among their population. Similarly among other member countries, a new resolve to shake off a legacy of high unemployment and to build "the most competitive economy in the world" mixes in some quarters with lingering apprehension that EU enlargement disrupts already strained labr markets. This volume contains the papers presented at the conference held in Baden, Austria, in June 2001 to investigate these questions. The content of this research work captures the thoughts and analysis of the senior policymakers, academics, and social partners who participated in this series of seminars. This digest of research work seeks to present the latest factual trends on labor issues in accession countries, reviews exisitng labor market policies and social protection mechanisms, and discusses alternative strategies for employment creation in Central and Eastern Europe.